Unterschiedliche Berufsinteressen als Einflussfaktor für die Einmündungschancen in betriebliche Ausbildung? Ein Vergleich zwischen männlichen und weiblichen Jugendlichen mit und ohne Migrationshintergrund - Ursula Beicht; Günter Walden (Journal for Labour Market Research, 2015)
– Numerous past studies dealing with the transition into initial vocational education and training in Germany have shown that young people with migration backgrounds have significantly poorer chances of ending up in in-company initial vocational education and training than those without migration backgrounds. The present article investigates whether possible deviations in career interests could explain the different chances of transition. Given that occupational preferences are still to a large extent influenced by a person's gender, distinctions are made in the analyses between male and female migrants and men and women without migration backgrounds. The underlying data is based on the representative surveys of reported training place applicants which were conducted in 2010 and 2012 by the Federal Institute for Vocational Education and Training (BIBB) in cooperation with the Federal Employment Agency (BA) (BA/BIBB Surveys of Applicants 2010 and 2012). With regard to deviations in career interests, the results show that young people with migration backgrounds are significantly more interested in service occupations than young people without migration backgrounds. This applies to men and women equally. However, the analyses show that migrants have poorer chances of transition into in-company initial vocational education and training even if the differences in career interests are taken into account. On the other hand, the different chances of transition of men and women can be attributed clearly to the deviations in career interests - both for migrants and non-migrants.
Keywords: 330; berufliche Integration - Determinanten; betriebliche Berufsausbildung; Geschlechterverteilung; ausländische Jugendliche; Migranten; erste Schwelle; Berufsinteresse